Countering the counterculture : rereading postwar American dissent from Jack Kerouac to Tomás Rivera - Martínez, Manuel Luis (University of Wisconsin Press, 2003)
"In an innovative rereading of American radical politics and culture of the 1950s and 1960s, Martinez uncovers reactionary, neoromantic, and sometimes racist strains in the Beats' vision of freedom, and he brings to the fore the complex stances of Latinos on participant democracy and progressive culture. He analyzes the ways the Beats, Chicanos, and migrant writers conceived of and articulated social and political perspectives. He contends that both the Beats' extreme individualism and the Chicano nationalists' narrow vision of citizenship are betrayals of the democratic ideal, but that the migrant writers presented a distinctly radical and inclusive vision of democracy that was truly countercultural."--Jacket